Strengthening Character Education in Children Through the Play Process and Learning Traditional Games - Maulida Maulida; Syarifah Farissi Hamama; Suryani; Putri Rizki Amalia; Ganesha Saputra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
FKIP Kindergarten is a Kindergarten with Accreditation B, and its address is at Jl. Inong Balee, PPG Dormitory, Kopelma Darussalam Village, Syiah Kuala District, Banda Aceh City, Aceh Province. The number of students in Kindergarten FKIP is 148 students and 16 teachers. FKIP Kindergarten has games in the schoolyard, but the focus of the games is more dominant on improving motor skills so that the increase in affective abilities becomes less honed. This dedication focuses on building children's character and increasing numeracy literacy through fun things. The method used in this service program is the direct instruction method, namely the service team consisting of 3 lecturers and 2 students assisted by partners, namely kindergarten teachers. With the giant snakes and ladders game, kindergarten students get an emphasis on character, literacy, and numeracy through games, so that character emphasis becomes easier to apply. The snakes and ladders provided have been specifically designed with additional characters and literacy and numeracy materials.